2018
DOI: 10.1002/jcp.26255
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid elongase7 is regulated via SP1 and is involved in lipid accumulation in bovine mammary epithelial cells

Abstract: Fatty Acid Elongase 7 (ELOVL7) is the newly discovered protein on human that catalyzes the rate-limiting step towards the synthesis of very long-chain fatty acids and exhibits the highest activity toward C18: 3 (n-3) acyl-CoAs, which is the precursor of eicosapentaenoic acid (EPA, 20: 5n-3). However, in ruminants, an overall understanding of ELOVLs gene family and the transcriptional regulation of ELOVL7 remain unknown. The purpose of this study is to investigate the transcriptional regulation and the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Therefore, we speculate that these two proteins may be associated with reduced sebum secretion in the elderly, leading to a dry and desquamating phenotype. Other upregulated DEPs included fatty acid elongase 7 (ELOVL7), which participates in the synthesis and extension of very long-chain fatty acids [ 28 ], and arachidonate 15-lipoxygenase B (ALOX15B), a key enzyme in the metabolism of polyunsaturated fatty acids. The latter finding deserves further scrutiny, since downregulation of ALOX15B gene expression in light-damaged skin has been reported previously [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that these two proteins may be associated with reduced sebum secretion in the elderly, leading to a dry and desquamating phenotype. Other upregulated DEPs included fatty acid elongase 7 (ELOVL7), which participates in the synthesis and extension of very long-chain fatty acids [ 28 ], and arachidonate 15-lipoxygenase B (ALOX15B), a key enzyme in the metabolism of polyunsaturated fatty acids. The latter finding deserves further scrutiny, since downregulation of ALOX15B gene expression in light-damaged skin has been reported previously [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…labrax fads 2 gene promoters without an Sp1 site showed lower activity, and thus it is speculated that the low expression of fads 2 can be attributed to their incomplete and less active promoter 11 , 17 . Recently, the Sp1 binding site was detected in mammalian FADS and ELOVL7 promoters, and Sp1 up-regulated the expression of Fads2 and Elovl7 40 , 41 . These results suggested that the lack of Sp1 binding site maybe a reason leading to the low promoter activity of fads 2, and thus result in low hepatic fads 2 expression in carnivorous marine teleost, like E .…”
Section: Discussionmentioning
confidence: 99%
“…Among those in goats, 2 positive correlations were observed between SCD5 and the milk desaturation ratios of cis-9 14:1/14:0 and cis-9,trans-11 18:2/trans-11 18:1, and 3 positive correlations were observed between LPL and cis-9,trans-11 CLA, trans-8,cis-10 CLA, and 20:3n-6; however, these associations require further investigation. Notably, specifically in cows, the transcription factor SP1 was correlated with the yield (g/d) of 14 individual FA (6:0, 8:0, cis-9 10: 1, iso-13:0, iso-14:0, iso-15:0, iso-16:0, 14:0, trans-9 14:1, anteiso-15:0, anteiso-17:0, cis-7 16:1, 18:3n-3, 24:0) or FA sum (C4-C14, <C16) or desaturation ratios, which require further investigation because of the role of this transcription factor in a wide range of cellular processes in mammalian cells (Chen et al, 2018).…”
Section: Mammary Metabolismmentioning
confidence: 99%